Crafting Better Futures: An NGO’s Educational Programs for Women Artisans in West Africa - Jill Zarestky (Adult Education Research Conference, 2014)
This qualitative case study centered on the educational programs of an international NGO working in West Africa to alleviate poverty and empower local women. Difficulty with cross-cultural communication and a lack of educational expertise diminished an otherwise successful organization’s efficacy.